2014
DOI: 10.1002/pi.4847
|View full text |Cite
|
Sign up to set email alerts
|

Multichromic polymers based on pyrene clicked thienylpyrrole

Abstract: Pyreneclicked SNS was subjected to electrochemical homo‐ and copolymerization. Copolymers exhibit multichromic behavior with low band gaps and switching times. Fine tuning of the colors was achieved through control of the copolymerization potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These characteristics have allowed the development of many technological applications [3], from organic and molecular electronic [4,5] to sensors [6][7][8] or smart surfaces [9][10][11][12][13]. Among many types of CPs, poly(thienyl-pyrrole-thienyl) derivatives have received great interest [14][15][16][17][18] especially for their electrochromic properties [19][20][21][22][23]. The structure of derivatives is generated from a central pyrrole units bearing two thiophene moieties attached on the C2 and C5 carbon atoms of the pyrrole and can be named SNS or Poly(SNS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics have allowed the development of many technological applications [3], from organic and molecular electronic [4,5] to sensors [6][7][8] or smart surfaces [9][10][11][12][13]. Among many types of CPs, poly(thienyl-pyrrole-thienyl) derivatives have received great interest [14][15][16][17][18] especially for their electrochromic properties [19][20][21][22][23]. The structure of derivatives is generated from a central pyrrole units bearing two thiophene moieties attached on the C2 and C5 carbon atoms of the pyrrole and can be named SNS or Poly(SNS).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many synthesis pathways have been developed to couple the SNS moieties and other monomers. Recently, Guven et al reported the synthesis of several SNS derivatives by click chemistry opening the way for new materials in electrochromic applications [20][21][22]. This approach allows one to achieve an effective post-polymerization functionalization of azide containing SNS monomer.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include SNS derivatives with substituted naphthalene group, 7 additional pyrrole group, 8 phenyl groups, [9][10][11] indan and 1,3-benzodioxole groups, 12 pyridinyl and phenanthroline groups, 13 benzoic acid group, 14 nitrophenyl group, 15 short alkyl groups 16 etc. Since the Paal-Knorr reaction can have relatively low yields, an innovative approach based on click chemistry has been proposed by our group leading to synthesis of SNS derivatives with substituted naphthalimide, 17 anthracene, 18 pyrene, 19 fluorene and carbazole units. 20 In addition, an ingenious approach, focused on click functionalization of the SNS polymer rather than the SNS monomer has been developed.…”
Section: The Novelty/significance Of Thiophene-pyrrole Hybrid Structuresmentioning
confidence: 99%
“…Recently, a number of SNS derivatives have been reported and displayed specific electrochromic properties. Camurlu et al synthesized anthracene- and pyrene-containing thienylpyrrole derivatives (SNS-Anth [24] and SNS-pyrene [25]) and reported their multichromic properties. Koyuncu et al reported the synthesis and electrochromic characterizations of a novel polymer (PSNS-PDI) consisting of SNS-donor and PDI-acceptor units [26].…”
Section: Introductionmentioning
confidence: 99%